Diseño y construcción de un ariete multipulsor con válvulas en disposición circular para el laboratorio de hidráulica de la carrera de ingeniería en electromecánica de la Universidad Nacional de Loja. - Pinto Guillín, María Catalina (2015)
The present thesis is addressed to proportionate improvements and to increase the capacity of an Multipress Battering Ram in order to place it at the Hydraulic Laboratory of the Electro-mechanic Engineering Career of the National University of Loja because the present Hydraulic Battering Rams in the market are expensive and their capacity is less than the proposal. Moreover, the Hydraulic lab does not have with this kind of Battering Ram, that is why, it has been necessary to design and build a Multipress Battering Ram with circular disposition valves. This study has been divided in three chapters that help to the effective development of work. The first chapter describes the use of water as a motor flow, as also the principle that is used in the Battering Ram punch, a complete diagram for the Battering Ram installation and its respective elements. The second chapter explains the essential theory for the hydraulic and mechanic design of the Multipress Battering Ram, the physic and chemic properties that must be taken into account for its correct design. The third chapter states the required calculations for the Multipress Battering Ram design with circular disposition, for its next building. After that, the building materials, operation diagrams, building and assembly are named as also the planes of each piece of the Multipress Battering Ram and as a whole. Then the analyzes and discussion of results are done for finally being able to write the conclusions and recommendations regarding the project.